Origins of Metabolic Pathology in Francisella-Infected Drosophila - Vincent, Crystal M.; Simoes da Silva, Carolina J.; Wadhawan, Ashima; Dionne, Marc S. (Frontiers in Immunology, 2020)
The origins and causes of infection pathologies are often not understood. Despite this, the study of infection and immunity relies heavily on the ability to discern between potential sources of pathology. Work in the fruit fly has supported the assumption that mortality resulting from bacterial invasion is largely due to direct host-pathogen interactions, as lower pathogen loads are often associated with reduced pathology, and bacterial load upon death is predictable. However, the mechanisms through which these interactions bring about host death are complex. Here we show that infection with the bacterium Francisella novicida leads to metabolic dysregulation and, using treatment with a bacteriostatic antibiotic, we show that this pathology is the result of direct interaction between host and pathogen. We show that mutants of the immune deficiency immune pathway fail to exhibit similar metabolic dysregulation, supporting the idea that the reallocation of resources for immune-related activities contributes to metabolic dysregulation. Targeted investigation into the cross-talk between immune and metabolic pathways has the potential to illuminate some of this interaction.